Method for identification and evaluation depth of penetration contact details-switching devices - Radko, I. (Енергетика і автоматика, 2015)
The article is devoted penetration method of determining the contact details of the heat equation in spherical coordinates. It is shown that as the size of the foundations of the arc are very small compared with the surface of the contact details of the calculation of the thermal regime of contact details is carried out using the method of point source. Determined temperature distribution electric arc during its combustion when switching electrical current when working.